Technology-Based Operational Plan Optimization for Warehousing Startup:Secure Stash Case Study - Denito, Steven Stevu; Indradewa, Rhian; Hamdi, Edi; Iskandar, Muhammad Dhafi; Edi , Edi (Universitas Nusantara PGRI Kediri, 2025)
Abstract This article examines technology-based operational planning strategies in the warehouse service industry through a case study of Secure Stash, a startup that provides storage services integrated with expedition partners, RFID technology, and a comprehensive digital system. This research aims to identify best practices in designing operational services, projecting revenue streams, and developing efficient and sustainable work systems. The study refers to operational literature by Edi Hamdi and Muhammad Dhafi Iskandar and employs a descriptive–analytical approach based on Secure Stash project documents. The results show that the application of Lean methods, process digitalization, and the implementation of standardized operational SOPs can significantly enhance efficiency and customer satisfaction.